PEMBERDAYAAN ANGGOTA KELOMPOKTANI MELALUI PEMANFAATAN JERAMI PADI PADA BUDIDAYA TANAMAN BUNGA KOL DI KECAMATAN TAROGONG KALER - Ainur Riza; Ait Maryani; Achmad Musyadar (Sekolah Tinggi Pariwisata Mataram, 2020)
Empowerment of farmer group members is an effort to improve the behavior of farmers in implementing technological innovations with the aim of increasing the level of welfare of agricultural actors. the spread of the Covid-19 virus inhibits farming activities because of the difficulty of extension agents accessing routine meetings and counseling to members of farmer groups, as well as the research activities carried out with limited data collection as information material. This study aims to descriptively analyze the level of empowerment of farmer group members through the utilization of rice straw in the cultivation of cauliflower plants, analyze the factors that influence the level of empowerment of farmer group members and formulate strategies to increase the empowerment of farmer group members through the utilization of rice straw in cabbage flower cultivation. This research was conducted from March to July 2020 in Mekarwangi Village and Jati Village, Tarogong Kaler District, Garut Regency. The population in this study were 127 people who were members of 4 groups of farmers from two villages. Sampling was done using Purposive Sampling. The number of initial samples obtained 56 people from the calculation using the Slovin formula with an error rate of 10%, from the field observations obtained a sample of 40 people then the sample was reduced to 40 people. Data were processed using descriptive analysis, multiple linear regression analysis and kendal's tau-b analysis. The results of the analysis at the level of empowerment of farmer group members are quite high with low skills. Empowerment of farmer group members is influenced by the role of extension workers and the role of farmer groups. Strategies in increasing the empowerment of farmer group members can be done through improving the skills of farmers by counseling and training, fostering farmer groups and increasing the role of extension workers.